Fat and liver transplantation: clinical implications. (25th June 2018) - Vinaixa, Carmen; Selzner, Nazia; Berenguer, Marina
Summary: Nonalcoholic steatohepatitis (NASH), with or without hepatocellular carcinoma, is a growing indication for liver transplantation (LT) worldwide, particularly in the Western world. Patients with NASH typically combine features of metabolic syndrome with cardiovascular comorbidities, which challenge pre‐LT evaluation, surgical approaches, post‐LT management, and outcomes. Post‐LT survival in NASH patients is excellent, similar to that achieved with other indications, particularly in the absence of cardiovascular comorbidities. Although disease recurrence on the liver allograft is common, progression to advanced disease is uncommon, at least in the short term. Whether this holds true with longer follow‐up remains to be determined. Owing to the increased prevalence of nonalcoholic fatty liver disease worldwide, along with a shortened organ pool donation in many countries, utilization of donor grafts with hepatic steatosis is now more common. Understanding the limitations of these grafts as well as potential mechanisms to improve graft quality and/or transplant outcome is clue for transplant centers. In this review, we will summarize current data on evaluation of NASH patients and whether it differs from that applied to other candidates, the natural history of NASH both pre‐ and post‐transplantation, emphasizing on waiting list management and recurrence of the original disease in the new graft as well as post‐transplant outcome. Finally, we will discuss the current use of steatotic liver donors and strategies to improve outcome when using this type of grafts.